Prediction of the Vistula Channel Development Between Wloclawek and Torun: Evaluation with Regard to the New Geological Survey - Babiński, Zygmunt; Habel, Michał; Chalov, Sergey (Quaestiones Geographicae, 2014)
The aim of this paper is to present the geological structure of the Vistula river valley floor as the modifying factor of fluvial processes and present the development conditions of the contemporary Vistula river channel, which underwent marked transformation due to bed erosion and lateral erosion below the Włocławek reservoir. The analysis of the geological data and the geological survey conducted at the study reach of the Vistula between Włocławek and Toruń resulted in an image of the geological structure of the channel bed along the longitudinal profile